2022
DOI: 10.1055/a-1734-7952
|View full text |Cite
|
Sign up to set email alerts
|

Complete polyp resection with cold snare versus hot snare polypectomy for polyps of 4–9 mm: a randomized controlled trial

Abstract: Background and study aims: Endoscopic screening with polypectomy reduces colorectal cancer (CRC) incidence. Incomplete polyp removal may attenuate the effect of screening. This randomized trial compared cold snare polypectomy (CSP) with hot snare polypectomy (HSP) regarding complete polyp resection. Patients and methods: We included patients ≥ 40 years at 8 hospitals in 4 countries who had at least one 4-9 mm non-pedunculated polyp detected at colonoscopy. Patients were randomized 1:1 to CSP or HSP. Biopsies f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 37 publications
(116 reference statements)
2
28
0
Order By: Relevance
“…Third, the IRR was strikingly different for serrated polyps (26 %) compared with adenomas (16 %), even if such differences were not statistically significant. This difference has also been reported by others 6 7 . Finally, in this study, as in numerous other studies of colonoscopy quality, the inter-endoscopist variation is large.…”
supporting
confidence: 90%
“…Third, the IRR was strikingly different for serrated polyps (26 %) compared with adenomas (16 %), even if such differences were not statistically significant. This difference has also been reported by others 6 7 . Finally, in this study, as in numerous other studies of colonoscopy quality, the inter-endoscopist variation is large.…”
supporting
confidence: 90%
“…Although some data 7,19,20 presented in the literature showed no definitive advantages of clipping after EMR for preventing PDB, especially for removal of 6-9 mm polyps. Lots of studies 5,[21][22][23][24][25] showed that clip closure after EMR of large colorectal lesions is cost effective, especially in patients with a high risk of bleeding.…”
Section: Discussionmentioning
confidence: 98%
“…A flow 10.3389/fmed.2023.1154411 chart of the trial selection process is shown in Figure 1. Fourteen articles compared HSP with CSP, (15,16,21,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) three articles compared HSP to EMR, (31, 36, 37) three articles compared CSP to CS-EMR, (31,38,39) two articles compared CSP to EMR, (31, 40) two articles compared CSP to UCSP, (41,42) one article compared CS-EMR to EMR, (43) one article compared UEMR to EMR, (44) and one article compared APC to HSP and CSP (33). All studies were published after 2010, and nine studies were multicenter studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Fourteen articles were included in the meta-analysis comparing CSP with HSP for small polyps, (15,16,21,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Seventeen articles were included in the network metaanalysis for 4-10 mm non-pedunculated polyps (27)(28)(29)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). The characteristics of the included studies are summarized in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%